2003
DOI: 10.1007/s00394-003-0422-6
|View full text |Cite
|
Sign up to set email alerts
|

Long chain polyunsaturate supplementation does not induce excess lipid peroxidation of piglet tissues

Abstract: The results show that dietary vitamin E effectively prevented lipid peroxidation at the LCP concentrations investigated and suggest that levels presently in infant formulas are sufficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
1
8
2
Order By: Relevance
“…(2008) recently concluded that TBARS measured in plasma increased in a dose‐responsive manner when fish oil was supplemented for 12 weeks to laying hens. In contrast with these latter study results, Sarkadi‐Nagy et al. (2003) reported that there is no influence of the amount of DHA present in the diet of piglets.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…(2008) recently concluded that TBARS measured in plasma increased in a dose‐responsive manner when fish oil was supplemented for 12 weeks to laying hens. In contrast with these latter study results, Sarkadi‐Nagy et al. (2003) reported that there is no influence of the amount of DHA present in the diet of piglets.…”
Section: Discussioncontrasting
confidence: 79%
“…Higher amounts of PUFA in the membrane results in a higher susceptibility to free radical attack and lipid peroxidation. This leads to a higher nutritional need for antioxidants as described in rabbits (van den Berg et al., 1991), broilers (Febel et al., 2008) and piglets (Sarkadi‐Nagy et al., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It is true that some animal studies have suggested that the consumption of the n-3 fatty acids may result in an elevation of reactive oxygen species (ROS), which could contribute to brain aging (Dimitrova-Sumkovska et al, 2006;Hatanaka et al, 2006;Obajimi et al, 2007). Other animal studies, however, have reported no change in ROS levels (Sarkadi-Nagy et al, 2003). Of particular importance, clinical studies have found no effect of high-dose PUFA supplementation on ROS production (Richard et al, 2008).…”
Section: Safety and Possible Side Effectsmentioning
confidence: 99%
“…The consumption of N-3 has been shown to result in the elevation of reactive oxygen species (ROS) [39,40]. In another study, it was documented that there was no change in ROS level after the administration of N-3 [41]. Yet, some other researchers reported that N-3 reduce lipid peroxidation, and so improve the activities of the antioxidant system [42].…”
Section: Discussionmentioning
confidence: 96%